A synthetic biology toolkit for rationally designing genetic circuits in Acinetobacter baumannii - Letrari, Sara; Faccincani, Lisa; Intini, Stefano; Ertan, Ilgin; Varaschin, Tommaso; Galiazzo, Francesca; Costanzo, Marco; D’angelo, Giorgia; Del Giudice, Valentina; Guarnieri, Luca; Martini, Alex; Picchi, Asia; et al. (Frontiers in Systems Biology, 2026)
IntroductionAntimicrobial resistance (AMR) poses a severe global health threat, with Acinetobacter baumannii among the critical AMR priorities highlighted by World Health Organization (WHO). This Gram-negative pathogen exhibits intrinsic resistance traits, exceptional environmental persistence, and high genomic plasticity, harboring resistance islands.MethodsTo combat AMR through synthetic biology, this study characterizes a library of BioBrick parts to be adopted in A. baumannii engineering and develops a modular CRISPR interference (CRISPRi) platform.ResultsKey components were characterized, including two plasmid vectors, a library of inducible and constitutive promoters, and a CRISPRi-mediated repression system; for the latter, a testbed for biofilm-related genes implicated in the downregulation of antibiotic resistance is also provided.DiscussionBy enabling tunable transcriptional control through the characterized promoters and ensuring the ability to downregulate gene expression via CRISPRi, this synthetic biology toolkit lays the foundation for the rational design of genetic circuits to study and counteract AMR in A. baumannii. The modular platform here characterized provides a valuable resource for the iGEM community to advance functional genomic approaches against this alarming global health challenge.